As paixões como fundamento da moral e da política no tratado da natureza humana de David Hume - Franca, Nevitta Maria Pessoa de Aquino (2009)
The purpose of this study was to briefly approach the influence of the passions in moral and political philosophy of David Hume in his major work: A Treatise of Human Nature. It was presented initially Hume’s philosophy of passions, its types and characteristics: primary, secondary, direct, indirect, violent, and calm passions; causes and subjects of passions. Thereafter, it was analyzed the relationship between causality and necessity, the action and natural determinism, natural and moral evidence. Moreover, it was demonstrated the concernment of reason in Hume’s ethics, and its role in determining the individual moral behavior. Yet, it was discussed the purely instrumental role of the reason in human’s behavior matter, and a moral rationalism criticism by Hume. It was also exposed, from an analysis of the 3rd Treatise Book, the fundamental tenets of Hume, according to which man possesses a moral sense, is guided by feelings - pleasure and suffering - and the passions are the ultimate criterion to shape their actions. Finally, it was investigated the concepts of artifice and society, through the simultaneous examination of the origin of justice, property and government.